2016
DOI: 10.1299/jamdsm.2016jamdsm0026
|View full text |Cite
|
Sign up to set email alerts
|

Frictional characteristics of clamp surfaces of aneurysm clips finished by laser processing

Abstract: An aneurysm clip is a medical instrument that is used intraoperatively to clip a ruptured cerebral aneurysm and reduce the risk of rebleeding. To prevent the clips from slipping off the aneurysm neck, it is very important to maintain a constant clamp force. A high frictional coefficient of the clip blades will also help prevent slippage between the clip blades and the blood vessel. In this study, to raise the frictional coefficients of the clip blades, we used a laser processing machine to produce clamp surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In order to provide some degree of objectivity in evaluating the respective retractors, the static frictional coefficient of each retractor was measured for both wet and dry conditions. In the case of retracting a lung, only the static parameters were considered, however dynamic measurement of the frictional coefficient is outlined in Isami et al 14 An image of the measurement procedure is shown in Fig. 11.…”
Section: Measurement Of Static Frictional Coefficientmentioning
confidence: 99%
“…In order to provide some degree of objectivity in evaluating the respective retractors, the static frictional coefficient of each retractor was measured for both wet and dry conditions. In the case of retracting a lung, only the static parameters were considered, however dynamic measurement of the frictional coefficient is outlined in Isami et al 14 An image of the measurement procedure is shown in Fig. 11.…”
Section: Measurement Of Static Frictional Coefficientmentioning
confidence: 99%
“…Thus, it is important to understand the influence of the surface profile on the scuffing resistance. The surface texture is well known as the surface profile modification parameter for low friction, less wear, and oil sump [7] [8] [9]. In addition, peening such as shot peening, cavitation peening, and laser peening can form the arbitrary surface profile with the changes in peening conditions to the metal surface.…”
Section: Introductionmentioning
confidence: 99%